Research on the wind pressure resistance and fracture capacity of windshield glass for rail vehicles - Chengxing Yang; Zhao Nan; Yujia Huo; Jiefu Liu; Liangzhong Xu; Huichao Huang (Results in Engineering)
This study aims to systematically analyse the wind pressure resistance and fracture capacity of train windshield glass, particularly considering the unique environmental conditions of the Lanzhou-Xinjiang Railway in China. Novel wind pressure testing systems were developed, including a hydrostatic test device, a hydraulic fatigue testing device, and a transient impact testing device using an air cannon. The research objectives were to determine the maximum static pressure causing windshield glass fracture, evaluate the likelihood of damage due to static pressure differences in a sandy environment, and assess the impact resistance and fatigue damage potential under dynamic conditions. Firstly, the windshield glass was subjected to steady-state uniform pressure loading until failure, establishing the maximum static pressure threshold. Comparative analysis with the static pressure differences experienced in a sandy environment was conducted to assess direct damage risks. Dynamic extreme impact loading tests using an air cannon identified the peak dynamic impact pressure capable of damaging the glass. Subsequently, the windshield glass underwent fatigue testing with ±4 kPa alternating loads for over 100,000 cycles to evaluate fatigue-induced damage potential. A constitutive relationship model of the windshield glass was employed in damage simulation calculations under dynamic wind pressure loads to investigate crack propagation processes and stress variations at crack tips. The results demonstrated that the windshield glass remained intact under transient pure air impact conditions at 69.4 kPa and did not break under 100,000 cycles of ±4 kPa alternating fatigue loads. Simulation results revealed that the crack propagation process is cyclical, involving phases of stress accumulation, crack propagation with energy release, stress reduction, and re-accumulation.